2021
DOI: 10.3390/ma14113095
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Alloy Formation of a WMoTaNbV Refractory Metal High Entropy Alloy by Laser Powder Bed Fusion (PBF-LB/M)

Abstract: High entropy or multi principal element alloys are a promising and relatively young concept for designing alloys. The idea of creating alloys without a single main alloying element opens up a wide space for possible new alloy compositions. High entropy alloys based on refractory metals such as W, Mo, Ta or Nb are of interest for future high temperature applications e.g., in the aerospace or chemical industry. However, producing refractory metal high entropy alloys by conventional metallurgical methods remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In the majority of cases, multicomponent alloys are synthesized by crystallization from the melt (arc or induction melting in vacuum or argon [5][6][7][13][14][15][16][17][18][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], plasma spark sintering [19], electric current assisted sintering [20,21], laser or plasma cladding deposition of coatings [44][45][46][47][48][49][50][51][52][53][54][55], additive manufacturing by the laser-powder bed fusion [56,57] or laser-metal deposition [58], self-propagating high-temperature synthesis (SHS) [59], and by brazing within the brazing joints [60,61]). Figure 1 shows a schematic phase diagram for the simplest case when there are on...…”
Section: Grain Boundary Wetting By the Liquid Phasementioning
confidence: 99%
“…In the majority of cases, multicomponent alloys are synthesized by crystallization from the melt (arc or induction melting in vacuum or argon [5][6][7][13][14][15][16][17][18][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], plasma spark sintering [19], electric current assisted sintering [20,21], laser or plasma cladding deposition of coatings [44][45][46][47][48][49][50][51][52][53][54][55], additive manufacturing by the laser-powder bed fusion [56,57] or laser-metal deposition [58], self-propagating high-temperature synthesis (SHS) [59], and by brazing within the brazing joints [60,61]). Figure 1 shows a schematic phase diagram for the simplest case when there are on...…”
Section: Grain Boundary Wetting By the Liquid Phasementioning
confidence: 99%
“…In the majority of cases, HEAs are manufactured by crystallization from the melt after arc or induction melting [5][6][7][8][9][10][11][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], electric current assisted sintering [35,36], plasma spark sintering [37], additive manufacturing by the laser powder bed fusion [38,39] or laser metal deposition [40], laser or plasma cladding deposition of coatings [41][42][43][44][45][46][47][48][49][50][51][52], selfpropagating high-temperature synthesis (SHS) [53], or even by brazing of dissimilar materials within the brazing joints [54,55]). In some cases, the liquid phase is not present during the synthesis of HEAs such as in the case of sputter deposition of coatings…”
Section: Grain Boundary Wetting By the Second Solid Phasementioning
confidence: 99%
“…Additionally, they found that under the same printing conditions (apart from the laser power), the density of the pre-alloyed powder samples was higher compared to that of the mix elemental powder samples. Other attempts to produce HEAs using mix elemental powder were carried out by Zhang et al [ 121 ], Huber et al [ 122 ], and Ron et. al.…”
Section: Additive Manufacturing (Am) Technologies Of High Entropy All...mentioning
confidence: 99%